PREDICTIVE VALUE OF OTHER COMPREHENSIVE INCOME: EVIDENCE FROM ASEAN - Rahayu, Puji; Kusuma, Indra Wijaya (UI Scholars Hub, 2020)
This paper examines the predictive value of other comprehensive income and its disclosure in ASEAN. Unlike value relevance, the predictive value of other comprehensive income has not been extensively addressed in the literature. We conduct the first study examining the predictive value of other comprehensive income and its disclosure to prove that not only fair value as relevant information, but also other comprehensive income reflecting the changes of fair value. We use hand-collected data taken from the financial reports. This study employs a panel regression model to test the ability of other comprehensive income and its disclosure to predict firms’ future performance. The results confirm that as relevant information, other comprehensive income and its disclosure have predictive value. In addition, other comprehensive income which interacted with disclosure of other comprehensive income resulted predictive value only for one year ahead. Furthermore, other comprehensive income components which belongs to fair value level 1 and 2 have predictive value because it uses market-based input. Meanwhile, other comprehensive components which belong to fair value level 3 only have predictive value for one year ahead because it uses unobservable input that can lead to higher subjectivity.